Crystal structures and magnetic properties of strontium and copper doped lanthanum ferrites - Natali Sora, Isabella; Caronna, Tullio; Fontana, Francesca; de Julián Fernández, César; Caneschi, Andrea; Green, Mark (Journal of solid state chemistry, 2012)
The crystal and magnetic structures of La0.8Sr0.2Fe1−xCuxO3−w compounds, which exhibit coercive fields larger than any others reported for iron-based perovskites, have been analyzed at room temperature with the neutron powder diffraction technique and the Rietveld method of profile fitting. For x in the range 0.05–0.10 the material is monophasic with orthorhombic symmetry (space group Pnma), and crystallizes in the perovskite-like cell of LaFeO3, Fe/Cu cations occupy octahedral sites, La/Sr cations are twelve-fold coordinated. For x=0.20 the material is biphasic, with a main orthorhombic phase (space group Pnma) and a secondary rhombohedral phase with space group R-3c (hexagonal setting). The structural transition from the orthorhombic to the rhombohedral phase reduces the structural distortion of the (Fe/Cu)O6 octahedron. The average bond distance (Fe/Cu)–O and the pseudo-cubic unit cell volume decrease with increasing Cu content in accordance with the presence of higher valence states of the transition metals. The magnetic structure was modeled for the monophasic samples (x=0.05 and 0.10) assuming an antiferromagnetic interaction between Fe/Cu neighboring cations (G-type): the magnetic moments order antiferromagnetically along the b-axis, with the spin direction along a-axis. The magnetic moments of the Fe/Cu atoms are μx=2.66(3)μB and 2.43(3)μB for the compositions x=0.05 and 0.10, respectively. By measuring the first magnetization curve and the hysteresis loops, coexisting antiferromagnetic and weak ferromagnetic interactions were observed for all samples. Hysteresis loops measured at room temperature of the sample with x=0.05. [Display omitted] ► Iron based perovskites with the largest coercive fields. ► Sr and Cu lanthanum ferrites as magnetic materials. ► Doped lanthanum ferrites show antiferromagnetic and weak ferromagnetic interactions. ► Sr and Cu lanthanum ferrites show distorted perovkite structure.